A novel aspirin prodrug inhibits NFκB activity and breast cancer stem cell properties. Issue 1 (December 2015) - Kastrati, Irida; Litosh, Vladislav; Zhao, Shuangping; Alvarez, Manuel; Thatcher, Gregory; Frasor, Jonna
Abstract Introduction Activation of cyclooxygenase (COX)/prostaglandin and nuclear factor κB (NFκB) pathways can promote breast tumor initiation, growth, and progression to drug resistance and metastasis. Thus, anti-inflammatory drugs have been widely explored as chemopreventive and antineoplastic agents. Aspirin (ASA), in particular, is associated with reduced breast cancer incidence but gastrointestinal toxicity has limited its usefulness. To improve potency and minimize toxicity, ASA ester prodrugs have been developed, in which the carboxylic acid of ASA is masked and ancillary pharmacophores can be incorporated. To date, the effects of ASA and ASA prodrugs have been largely attributed to COX inhibition and reduced prostaglandin production. However, ASA has also been reported to inhibit the NFκB pathway at very high doses. Whether ASA prodrugs can inhibit NFκB signaling remains relatively unexplored. Methods A library of ASA prodrugs was synthesized and screened for inhibition of NFκB activity and cancer stem-like cell (CSC) properties, an important PGE2-and NFκB-dependent phenotype of aggressive breast cancers. Inhibition of NFκB activity was determined by dual luciferase assay, RT-QPCR, p65 DNA binding activity and Western blots. Inhibition of CSC properties was determined by mammosphere growth, CD44+ CD24− immunophenotype and tumorigenicity at limiting dilution. Results While we identified multiple ASA prodrugs that are capable of inhibiting the NFκB pathway, several were associated with cytotoxicity. Of particular interest was GTCpFE, an ASA prodrug with fumarate as the ancillary pharmacophore. This prodrug potently inhibits NFκB activity without innate cytotoxicity. In addition, GTCpFE exhibited selective anti-CSC activity by reducing mammosphere growth and the CD44+ CD24− immunophenotype. Moreover, GTCpFE pre-treated cells were less tumorigenic and, when tumors did form, latency was increased and growth rate was reduced. Structure-activity relationships for GTCpFE indicate that fumarate, within the context of an ASA prodrug, is essential for anti-NFκB activity, whereas both the ASA and fumarate moieties contributed to attenuated mammosphere growth. Conclusions These results establish GTCpFE as a prototype for novel ASA-and fumarate-based anti-inflammatory drugs that: (i) are capable of targeting CSCs, and (ii) may be developed as chemopreventive or therapeutic agents in breast cancer.